2017
DOI: 10.1556/018.68.2017.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Physiological role of exogenous nitric oxide in improving performance, yield and some biochemical aspects of sunflower plant under zinc stress

Abstract: The present study was undertaken to examine the possible roles of sodium nitroprusside in protection against oxidative damage due to zinc toxicity in sunflower plants. Physiochemical parameters in sunflower plants exposed to Zn (100, 200 and 300 mg/kg soil) alone or combined with SNP were measured. The results showed that excess of Zn decreased plant growth, seed yield components and photosynthetic pigments content. On the other hand, Zn stress increased the level of non-enzymatic antioxidants (ascorbic acid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The application of Zn may restore distorted chlorophyll assimilation attributable to sodium chloride ( Figure 1 d; [ 3 ]). Zinc probably keeps chlorophyll assimilation through the protection of the sulphydryl group and improved Mg uptake [ 34 , 35 , 36 ]. Paclobutrazol application has been documented to boost chlorophyll under normal or stress conditions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of Zn may restore distorted chlorophyll assimilation attributable to sodium chloride ( Figure 1 d; [ 3 ]). Zinc probably keeps chlorophyll assimilation through the protection of the sulphydryl group and improved Mg uptake [ 34 , 35 , 36 ]. Paclobutrazol application has been documented to boost chlorophyll under normal or stress conditions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of Zn and PBZ on seed carbohydrate content would be related to the increase in starch synthase and CA activity, as well as improved Rubisco activity that improves seed development [ 51 , 52 , 53 ]. Additionally, zinc application is recognized to preserve enzyme activity through binding the sulphydryl group, and hence defending disulfide formation that leads to a rise in protein biosynthesis and protein content in the seed [ 34 , 35 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The total soluble protein (TSP) in the leaves of watermelon plants experienced non-significant effects under excess boron and the application of SA but increased for the SA-treated plants compared to the non-stressed and stressed plants ( Figure 6) [74,75]. SA induced a considerable increase in the content of protein fractions in sunflower plants under Cu stress [76] and chamomile plants under Cd and Ni stresses [77].…”
Section: Discussionmentioning
confidence: 99%
“…In general, NO‐mediated protection against Zn toxicity is tightly correlated with an improved antioxidant response (Table ). For instance, the exogenous application of SNP (20 µM) in Helianthus annuus plants exposed to Zn (100, 200 and 300 mg kg −1 soil) led to a higher degree of tolerance, with an upregulation of the main antioxidant enzymes, such as SOD, APX, GR, and metabolites (AsA and GSH; Akladious and Mohamed ). In a similar way, studying the potential phytotoxicity of zinc oxide nanoparticles (nano‐ZnO; at 0, 5, 10, 25, 50 and 100 µM), Chen et al () reported that NO (SNP – 10 µM) prevented nano‐ZnO macroscopic toxicity and reduced Zn uptake and accumulation.…”
Section: No‐mediated Regulation Of Metal‐induced Oxidative Stressmentioning
confidence: 99%